Antidiabetic Activity of Ethanol Extract of Robusta Coffee (Coffea canephora) Leaves in Alloxan-Induced Mice (Mus musculus) - Sarah Zaidan; Heryanti Borotoding (Journal of Pharmacy and Clinical Practice, 2025)
Robusta coffee leaves are widely used by the community as a drink to lower blood glucose levels. According to several studies, robusta coffee leaves have a hypoglycemic effect because they contain bioactive compounds that are useful for lowering blood glucose levels. The purpose of this study was to determine the antidiabetic activity of the ethanol extract of robusta coffee leaves in alloxan-induced mice. In this study, mice were divided into 6 groups each consisting of 5 mice. Group I normal control, group II negative control was given 0.5% Na CMC, group III positive control was given acarbose 1%, group IV, V, and VI were treated with ethanol extract of robusta coffee leaves in successive doses of 50, 100, and 200 mg/kg body weight. Mice group II, III, IV, V, and VI were made hyperglycemic by inducing alloxan 200 mg/kgBW intraperitoneally. Mice blood was taken through a lateral vein and blood glucose levels were measured using a glucometer. The research data were analyzed using statistical analysis. The results of the study showed a decrease in blood glucose levels in group IV 25.1%, group V 40.9% and group VI 56.7%. Based on the results of this study, it can be concluded that the ethanol extract of robusta coffee leaves has antidiabetic activity which can reduce blood glucose levels in mice induced by alloxan and the optimal dose to reduce blood glucose levels is 200 mg/kgBW. The research data were analyzed using statistical analysis. The results of the study showed a decrease in blood glucose levels in group IV 25.1%, group V 40.9% and group VI 56.7%. Based on the results of this study, it can be concluded that the ethanolic extract of robusta coffee leaves has antidiabetic activity which can reduce blood glucose levels in mice induced by alloxan and the optimal dose to reduce blood glucose levels is 200 mg/kgBW. The research data were analyzed using statistical analysis. The results of the study showed a decrease in blood glucose levels in group IV 25.1%, group V 40.9% and group VI 56.7%. Based on the results of this study, it can be concluded that the ethanolic extract of robusta coffee leaves has antidiabetic activity which can reduce blood glucose levels in mice induced by alloxan and the optimal dose to reduce blood glucose levels is 200 mg/kgBW. Keywords: Diabetes mellitus, Coffea canephora, alloxan.